Identification of a novel pathogenic Borrelia species causing Lyme borreliosis with unusually high spirochaetaemia: a descriptive study. Issue 5 (May 2016) - Pritt, Bobbi S; Mead, Paul S; Johnson, Diep K Hoang; Neitzel, David F; Respicio-Kingry, Laurel B; Davis, Jeffrey P; Schiffman, Elizabeth; Sloan, Lynne M; Schriefer, Martin E; Replogle, Adam J; Paskewitz, Susan M; Ray, Julie A; et al.
Summary: Background: Lyme borreliosis is the most common tick-borne disease in the northern hemisphere. It is a multisystem disease caused by Borrelia burgdorferi sensu lato genospecies and characterised by tissue localisation and low spirochaetaemia. In this study we aimed to describe a novel Borrelia species causing Lyme borreliosis in the USA. Methods: At the Mayo clinic, from 2003 to 2014, we tested routine clinical diagnostic specimens from patients in the USA with PCR targeting the oppA1 gene of B burgdorferi sensu lato. We identified positive specimens with an atypical PCR result (melting temperature outside of the expected range) by sequencing, microscopy, or culture. We collected Ixodes scapularis ticks from regions of suspected patient tick exposure and tested them by oppA1 PCR. Findings: 100 545 specimens were submitted by physicians for routine PCR from Jan 1, 2003 to Sept 30, 2014. From these samples, six clinical specimens (five blood, one synovial fluid) yielded an atypical oppA1 PCR product, but no atypical results were detected before 2012. Five of the six patients with atypical PCR results had presented with fever, four had diffuse or focal rash, three had symptoms suggestive of neurological inclusion, and two were admitted to hospital. The sixth patient presented with knee pain and swelling. Motile spirochaetes were seen in blood samples from one patient and cultured from blood samples from two patients. Among the five blood specimens, the median oppA1 copy number was 180 times higher than that in 13 specimens that tested positive for B burgdorferi sensu stricto during the same time period. Multigene sequencing identified the spirochaete as a novel B burgdorferi sensu lato genospecies. This same genospecies was detected in ticks collected at a probable patient exposure site. Interpretation: We describe a new pathogenic Borrelia burgdorferi sensu lato genospecies (candidatus Borrelia mayonii ) in the upper midwestern USA, which causes Lyme borreliosis with unusually high spirochaetaemia. Clinicians should be aware of this new B burgdorferi sensu lato genospecies, its distinct clinical features, and the usefulness of oppA1 PCR for diagnosis. Funding: US Centers for Disease Control and Prevention Epidemiology and Laboratory Capacity for Infectious Diseases (ELC) Cooperative Agreement and Mayo Clinic Small Grant programme.